THE INFLUENCE OF JOB RESOURCES, PUBLIC SERVICE MOTIVATION ON ORGANIZATIONAL ENGAGEMENT WITH WORK ENGAGEMENT AS A MEDIATOR - Ari Kuswantoro; Riani Rachmawati (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
The objective of this research is to examine the impact of job resources and public service motivation on organizational engagement with work engagement as a mediator among tax education functional officers at the national tax authority. The research employed a quantitative approach using a survey method of 210 tax education functional officers, while the data were analyzed using SEM. The findings indicated that job resources and public service motivation had positive and significant effects on work engagement. Job resources had a positive and significant effect on organizational engagement, while public service motivation did not significantly influence organizational engagement. Work engagement proved to be a strong mediator in the relationship between job resources and public service motivation towards organizational engagement. The research model explained 49% of the variation in organizational engagement and 27% of the variation in work engagement. These findings provide implications for the national tax authority in developing effective management strategies for tax education functional officers by considering aspects of job resources and public service motivation to enhance work engagement and organizational engagement.